Spreading of drill cuttings and sediment recovery of three exploration wells of different ages, SW Barents Sea, Norway. (October 2018) - Junttila, Juho; Dijkstra, Noortje; Aagaard-Sørensen, Steffen
Abstract: Five stations (≤250 m from the well heads) from three exploration wells of different ages from the SW Barents Sea were studied to investigate the spreading of drill cuttings and sediment quality. Two of the wells were drilled before the restriction of use of oil-based drilling fluids (1993). Elevated concentrations of Ba were found in sediments near all the wells with the highest concentrations at ≤60 m from the well head. The thickness of drill cutting layers was between >20 cm (well head) and 2 cm (250 m from the well head). The sediment quality varied from very bad (oldest well) to background (normal) (newer wells). Regulations led to better sediment quality. Metal concentrations from the oldest well suggested that the top 4 cm of the core represents sediment recovery. However, Ba concentrations of the top sediment layer at all the stations of the three wells indicate no physical recovery. Highlights: Drill cuttings were studied in sediments <250 m away from different age wells. Elevated concentrations of Ba are found in all of the wells ≤60 m from the wellhead. The drill cutting layers are from >20 cm (wellhead) to 2 cm (250 m from wellhead) thick. The sediment quality varies from very bad (oldest well) to background (newer wells). Regulations in 1993 and after led to improving effect on the sediments quality.